Analisis Respon Guru Terhadap Pengembangan Booklet Pembelajaran Biologi Pada Materi Permasalahan Lingkungan dan Upaya Mengatasinya Terintegrasi Budaya Lokal Masyarakat Paninjauan, Tanah Datar - Lestari, Yulia; Arsih, Fitri (Edusainstika: Jurnal Pembelajaran MIPA, 2024)
This study aims to develop a Biology learning booklet on the topic of "Environmental Issues and Mitigation Efforts" integrated with the local culture of the Paninjauan community in Tanah Datar, as well as to analyze teachers' responses to its development. The booklet is designed to reintroduce local cultural values to students, support the preservation of fading traditions, and enhance motivation to learn Biology through contextual and engaging materials. This research employs a qualitative method, collecting data through questionnaires and interviews involving Biology teachers from various high schools as participants. The findings reveal that the booklet received positive feedback from teachers. It is considered visually appealing and content-rich, making it relevant for Biology learning, as it effectively increases students' motivation while reinforcing local cultural values. Teachers highlighted that integrating local culture into Biology learning is an effective way to achieve holistic educational goals. Therefore, this booklet is deemed suitable as a supplementary learning resource to enrich Biology education and promote the preservation of local cultural values.